SMART PHONE OVERUSE AMONG SENIOR SECONDARY SCHOOL STUDENTS IN RELATION TO STUDY HABITS - Indu Sharma 1, Dr. Baby Nilam 2 (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Smart phone is strongly used by young people which affect their day-to-day life in all aspects. The present research aims to investigate smartphone overuse among senior secondary school students of district Kangra in relation to their study habits. The study was descriptive and quantitative in nature. The sample of the study was selected by Simple Random Sampling technique. It included 200 (100 male and 100 female) students from 5 government and 5 private schools of district Kangra (Himachal Pradesh). The tools were used for the research Smartphone Addiction Scale and Study Habits Scale by Vijayshri and Masaud Ansari and Rani and Jaidka respectively. The statistical technique Pearson correlation coefficient was used to analyse the data. The research finding reveals that there is no relationship between senior secondary school students’ excessive usage of smartphones and their study habits. Furthermore, research indicates a significant relationship between overuse of smartphones by male students studying in senior secondary schools and their study habits. Additionally, there was no correlation discovered in the study habits of female senior secondary school pupils and their excessive smartphone use. Consequently, it is suggested that school officials instruct students about the negative aspects of smartphones, highlighting that utilising them in moderation can enhance study habits and utilising them in excess will worsen them.